2018 IEEE 15th International Symposium on Biomedical Imaging (ISBI 2018) 2018
DOI: 10.1109/isbi.2018.8363576
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic data augmentation using GAN for improved liver lesion classification

Abstract: In this paper, we present a data augmentation method that generates synthetic medical images using Generative Adversarial Networks (GANs). We propose a training scheme that first uses classical data augmentation to enlarge the training set and then further enlarges the data size and its diversity by applying GAN techniques for synthetic data augmentation. Our method is demonstrated on a limited dataset of computed tomography (CT) images of 182 liver lesions (53 cysts, 64 metastases and 65 hemangiomas). The cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
302
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(345 citation statements)
references
References 12 publications
2
302
0
2
Order By: Relevance
“…Because in such level of accuracy, sometimes the so-called improvement is just one kind of overfitting to the current data set. Moreover, some recent studies validate the effectiveness of using synthetic images in a low-data regime (Antoniou et al, 2017;Frid-Adar et al, 2018;Salimans et al, 2016;Zhang et al, 2018). Thus, in this section, a special case under the condition of complex detection problem, low-data regime, and restricted computational power is designed and discussed.…”
Section: Synthetic Data Aggregation and Fine-tuningmentioning
confidence: 92%
See 1 more Smart Citation
“…Because in such level of accuracy, sometimes the so-called improvement is just one kind of overfitting to the current data set. Moreover, some recent studies validate the effectiveness of using synthetic images in a low-data regime (Antoniou et al, 2017;Frid-Adar et al, 2018;Salimans et al, 2016;Zhang et al, 2018). Thus, in this section, a special case under the condition of complex detection problem, low-data regime, and restricted computational power is designed and discussed.…”
Section: Synthetic Data Aggregation and Fine-tuningmentioning
confidence: 92%
“…Antoniou, Storkey, and Edwards (2017) proposed Data Augmentation GAN (DAGAN) and compared the performance of DAGAN trained classifier with other basic ones based on Omniglot, EMNIST, and VGG-Face data sets, showing promising enhancement. Frid-Adar, Klang, Amitai, Goldberger, and Greenspan (2018) applied DCGAN to generate synthetic medical images and proposed a training scheme by adding synthetic images. The classification performance with synthetic data augmentation outperformed the classical augmentation method with 7% improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Mok et al [55] reported that a PGGAN-based augmentation improved the dice coefficient of segmentation of a brain tumor by 0.03 (0.81 → 0.84) over a traditional augmentation approach. Frid-Adar et al [56] reported that a DCGAN-based augmentation improved the classification of a liver lesion by 7.1% (78.6% → 85.7%) in sensitivity and 4.0% (88.4% → 92.4%) in specifity over a traditional augmentation approach.…”
Section: Unconditional Synthesismentioning
confidence: 99%
“…In [12], a SVM model was used for feature selection in gait classification of leg length and distal mass. A discussion on synthetic data augmentation using generative adversarial networks for improved liver classification is provided in [13].…”
Section: Related Workmentioning
confidence: 99%